Mengatasi Krisis Moral Dalam Pendidikan Sekolah Dasar Di Masa Kini - Friska Anggraini S; Inka Fitriyani; Checilia Melita S; Nela Rofisian (CV. ITTC INDONESIA, 2023)
Our country grapples with a significant challenge in basic education—the pervasive issue of low morale. The importance of instilling morals from an early age cannot be overstated, focusing on the awareness of human dignity and rights. Elementary schoolchildren face a moral crisis exacerbated by factors like social media, foreign cultural influences, the absence of role models, diminished parental and teacher involvement, and an unsupportive environment. Employing a literature study approach and library research, this study utilizes various materials to gather data, such as documents, books, magazines, and historical stories. The aim is to address the moral crisis in elementary schools, providing therapeutic solutions and fostering character development in basic education. The role of parents and teachers is pivotal in family and school education, influencing moral values and personality development. This journal seeks to elucidate the crucial role parents and teachers play in instilling moral values in children through family education, moral education, and school education.